Comparative study of anthropometric measurement and body composition between junior basketball and volleyball players from Serbian national league - Masanovic, B. (SportMont, 2018)
The purpose of this study was to describe anthropometric characteristics and body composition of junior basketball and volleyball players from Serbian national league and to make comparison between them. Fifty-nine males were enrolled in the study divided into three groups: thirteen basketball players, fourteen volleyball players and thirty-two healthy sedentary subjects. All subjects were assessed for the anthropometric measures required for the calculation of body composition variables, using standardized procedure recommended by established literature. Data was analyzed using SPSS and the descriptive statistics were expressed as mean (SD) for each variable, while ANOVA and LSD Post Hoc tests were carried out to detect the effects of each type of sport. The results showed there was no significant difference in body mass index and bone content of body among the groups, while a significant difference was found for body height, body weight, muscle and fat contents of body among the groups. Basketball and volleyball players were significantly taller and heavier than the subjects of the control group, while there was not any significant difference between the body height and body weight of basketball and volleyball players. Muscle content of basketball players was significantly higher than control subjects, while a significant difference was not noticed between volleyball players and subjects of control group. Fat content in the body of basketball and volleyball players are significantly lower than the percent of fat content in the body of control group, while there was not found any other difference in this content. These findings may give coaches from the region better working knowledge and suggest them to follow recent selection process methods and to be more careful during the recruitment.